Stories, statistics, and memory - Thomas Wilhelm Graeber; Christopher Roth; Florian Zimmermann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
Widespread misperceptions shape attitudes on key societal topics, such as climate change and the recent pandemic. These belief distortions are puzzling in contexts where accurate statistical information is broadly available and attended to. This column argues that the nature of human memory may be key for understanding the persistence of misperceptions in practice. It documents that anecdotal information in the form of stories comes to mind more easily than statistical information, generating the potential for systematic belief biases.
Keywords: 330